Toxicity and phototoxicity in human ARPE-19 retinal pigment epithelium cells of dyes commonly used in retinal surgery. Issue 4 (July 2018) - Awad, Doaa; Wilińska, Joanna; Gousia, Dimitra; Shi, Xiaoye; Eddous, Jnina; Müller, Arne; Wagner, Veit; Hillner, Charlie; Brannath, Werner; Mohr, Andreas; Gabel, Detlef
Purpose: To compare, for the first time, systematically the toxicity and phototoxicity of dyes and dye combinations used in vitreoretinal surgery. The dyes were trypan blue, brilliant blue G, trypan blue + brilliant blue G, indocyanine green, bromophenol blue, bromophenol blue + brilliant blue G, and acid violet 17, in clinically used concentrations. Methods: Human ARPE retinal pigment epithelium cells were exposed to the dyes for 30 min. For phototoxicity, the cells were exposed for 15 min to high-intensity light from a light emitting diode source with an intensity similar to surgical conditions. Toxicity was assayed either directly after exposure to either dye alone or dye and light, or with a delay of 24 h. Results: None of the dyes or their combinations was toxic when cells were exposed to them at ambient light. Acid violet led to a reduction viability by 90% already immediately after light exposure. Bromophenol blue and its combination with brilliant blue G showed strong phototoxicity (reduction of viability by 83%) when assayed with delay. Indocyanine green with different agents to adjust osmolarity (balanced salt solution, glucose, and mannitol) was not found to be toxic. Conclusion: The strong immediate phototoxicity of acid violet reflects its clinical toxicity. Bromophenol blue might also be disadvantageous for patient outcome because of its delayed phototoxicity. The other dyes (trypan blue, brilliant blue g, and indocyanine green) were not found to be toxic neither with exposure to ambient light nor after exposure to light of intensities used in surgery.